Effects of micro-grooves on tribological behaviour of plasma-sprayed alumina-13%titania coatings. Issue 8 (1st June 2017) - Wahab, J.A.; Ghazali, M.J.; Sajuri, Z.; Otsuka, Y.; Jayaprakash, M.; Nakamura, S.; Baharin, A.F.S.
Abstract: This study was aimed at investigating the effects of micro-grooves on the tribological behaviour of a plasma-sprayed Al2 O3 – 13%TiO2 coating. A combined surface profile with non-regular depths and micro-groove texture was successfully developed by using a Nd:YVO4 laser system. The surface condition and characterisation of the Al2 O3 – 13%TiO2 coating was conducted using a VPSEM and a 3D microscope. A pin-on-disc test was then carried out to measure the effectiveness of the micro-grooves in reducing the wear rates of the Al2 O3 – 13%TiO2 coatings under non-lubricated conditions. It was noted that the textured coatings gradually decreased the wear rate with only a slight reduction on the friction coefficient due to the entrapment of the wear debris within the grooves. It was proven that the combined surfaces successfully reduced the wear rate up to 44.7% and 61.5% for 10 N and 20 N of load respectively.